More than a feeling: A unified view of stress measurement for population science - Epel, Elissa S.; Crosswell, Alexandra D.; Mayer, Stefanie E.; Prather, Aric A.; Slavich, George M.; Puterman, Eli; Mendes, Wendy Berry (Frontiers in neuroendocrinology, 2018)
•Stress research is limited by measurement issues and lack of common definitions.•We present a Stress Typology, common language for describing stress measurement.•A transdisciplinary model of stress merges epidemiological and psychological perspectives.•Historical stress shapes current psychological and physiological stress reactivity.•We describe the conscious and unconscious features of acute stress processes. Stress can influence health throughout the lifespan, yet there is little agreement about what types and aspects of stress matter most for human health and disease. This is in part because “stress” is not a monolithic concept but rather, an emergent process that involves interactions between individual and environmental factors, historical and current events, allostatic states, and psychological and physiological reactivity. Many of these processes alone have been labeled as “stress.” Stress science would be further advanced if researchers adopted a common conceptual model that incorporates epidemiological, affective, and psychophysiological perspectives, with more precise language for describing stress measures. We articulate an integrative working model, highlighting how stressor exposures across the life course influence habitual responding and stress reactivity, and how health behaviors interact with stress. We offer a Stress Typology articulating timescales for stress measurement – acute, event-based, daily, and chronic – and more precise language for dimensions of stress measurement.